Is Post-ERCP Pancreatitis a Genetically Predisposed Complication?. (15th August 2012) - Mystakidis, Konstantinos; Kouklakis, George; Papoutsi, Androniki; Souftas, Vasilios D.; Efremidou, Eleni; Kapetanos, Dimitrios; Pitiakoudis, Michail; Lyratzopoulos, Nikolaos; Karagiannakis, Anastasios; Pantelios, Alexandros
Abstract : Background/Objectives . Pancreatitis remains the most common complication of ERCP. History of post-ERCP pancreatitis is an independent risk factor for a new episode, suggesting a genetic background. The N34S mutation in serine protease inhibitor Kazal type 1 (SPINK 1) gene may downregulate the threshold for the development of pancreatitis. The aim of the present study is to evaluate the presence of this mutation among patients with post-ERCP pancreatitis. Methods . During a period of four years, thirty patients with post-ERCP pancreatitis entered the study. Patients and procedural data were collected, focusing on risk factors for pancreatitis. Blood samples were taken for genetic testing for the presence of N34S mutation in SPINK 1 gene. After DNA extraction, we used an allele-specific polymerase chain reaction as an initial screening method for the N34S mutation, and in order to confirm the results and to determine the hetero- and homozygosity genotype status, we used a restriction fragment length polymorphism (RFLP) method. Results . None of the thirty patients was found to carry the N34S mutation, with both of the applied methods. Patients had an average of two of the known risk factors. Conclusion . SPINK1 N34S mutation does not seem to play a role in post-ERCP pancreatitis, but larger studies needed to confirm our results.